The Dynamics of Religious Influence on the National Legal System of Indonesia - Yuliyanti, Sri; Nur Savinna, Dea; NurFauzi, Teguh (Decision, 2024)
This essay critically examines the growing discrepancies between the Federal Constitution (FC) of Indonesia and recently proposed or modified legislation, such as the planned RUU355, the Mufti Bill (now in its third reading), and Act 342 (currently being introduced). According to scholars like Harding (2012) and Thio (2006), the Federal Constitution is Indonesia's supreme law and is intended to uphold the principles of democracy, the rule of law, and the separation of church and state. But these core ideas seem to be undermined by contemporary legal trends, particularly in light of the expanding power of Islamic law and religious authority (Fernando, 2006; Ahmad, 2014). The aforementioned legislative reforms, which show a shift towards a more Islamic style of governance, have generated discussions regarding their consistency with Indonesia's secular constitutional framework (Hashim, 2018). This study examines the ways in which these legislative proposals violate constitutional protections such as freedom of religion (Lai, 2003), equal treatment under the law (Yatim, 2011), and judicial independence (Harding, 2018). The article adds to the continuing discussion on the constitutional limits of religious influence in Indonesia's legal and political system by analysing the ramifications of these statutes and bills. According to scholars like Shad Saleem Faruqi (2019) and Ibrahim (2002), unrestrained legislative interventions could drastically alter the constitutional balance and have a substantial impact on the legal and social fabric of the country.